The Simplest Test of Target Zone Credibility : The Simplest Test of Target Zone Credibility. (IMF Working Papers; Working Paper ;, 1990)
Under the assumption of no arbitrage exchange rate target zone credibility is tested by whether domestic interest rates fall within "rate-of-return bands" between the maximum and minimum home-currency rate of return on a foreign investment absent a devaluation. Under the assumption of uncovered interest rate parity credibility is tested by whether expected future exchange rates fall within the exchange rate band. These tests are applied on data about the Swedish target zone during January 1987-August 1990.